Motivações e repercussões da formação em agricultura biológica em contexto urbano: uma abordagem sociológica - Parente, Cristina; Santos, Rui; Ramos, Madalena (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2020)
In a sociological perspective, this article evaluates the motivations and the formative repercussions of the frequency of training in organic farming from an extensive approach based on a survey online. The results reveal a change to healthy eating behaviours, notably marked by the consumption of organic foods. While at the same time, due to increased physical activity, revealing positive health effects, and well-being as well as reduced stress and tiredness. There seems to be a tendency for quality of life improvement, while at the greater environmental awareness. However, attending the course was not an opportunity to change their professional activity